Synthetic measurement of deviation in budgetary control - Dynowska, Joanna; Kes, Zdzisław (Syntetyczny pomiar zróżnicowania odchyleń w kontroli budżetowej, 2018)
Budget control is an important element of budgeting, which is an important management accounting tool. Hence, it is necessary to recognize the need for its development. The article presents the authors’ method of measuring the variation of budget deviations. A synthetic measure of budget differentiation can be used to assess deviation levels in the budgetary control process. The method described herein provides a deviation measure that is a weighted average of the relative and absolute deviations using a convex combination of Gini coefficients, which are used as a measure of variance. The research used data including monthly budgeted and actual costs from a thermal power plant in Poland for the years 2014 through 2016. The article is a methodological approach that fits into the current research on tools used in budgetary control. In addition, the described method is integrated into the development of work on control systems
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2018, Nr 503, s. 133-142
Keywords: budget control; Gini coefficient; convex combination; kontola budżetowa; współczynnik Giniego; kombinacja wypukła